The Correlation between Students’ Vocabulary Mastery and Their Reading Comprehension Achievement - Kurniati Intan Samsini; Engelina Salainti; Meily Ivane Esther Neman; Elizabeth M. M. Lasut (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study aimed to investigate the levels of vocabulary mastery and reading comprehension achievement among ninth-grade students at SMPN 2 Airmadidi, North Sulawesi, and to determine whether a significant correlation exists between these two linguistic variables. Utilizing a quantitative correlational research design, a sample of 32 students was selected from the population. Data were gathered through two distinct instruments adapted from the official grade IX English textbook Bright an English: a vocabulary mastery test focusing on word classes and meanings, and a reading comprehension test evaluating main idea identification, literal comprehension, and contextual vocabulary inference. To ensure data integrity, an initial pilot study was conducted to analyze instrument validity and reliability. The empirical results indicate that students with higher levels of vocabulary mastery consistently demonstrate stronger reading comprehension capabilities. The data reject the null hypothesis (Ho), confirming a positive, meaningful connection where expansive vocabulary knowledge functions as a critical determinant of textual comprehension success. The pedagogical implications suggest that English teachers should implement explicit vocabulary enhancement strategies to systematically scaffold students' secondary reading achievements.